2011
DOI: 10.1371/journal.pone.0028103
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Regulation of HDAC2 Mediates Proliferation of Hepatocellular Carcinoma Cells by Deregulating Expression of G1/S Cell Cycle Proteins

Abstract: Histone deacetylase 2 (HDAC2) is crucial for embryonic development, affects cytokine signaling relevant for immune responses and is often significantly overexpressed in solid tumors; but little is known about its role in human hepatocellular carcinoma (HCC). In this study, we showed that targeted-disruption of HDAC2 resulted in reduction of both tumor cell growth and de novo DNA synthesis in Hep3B cells. We then demonstrated that HDAC2 regulated cell cycle and that disruption of HDAC2 caused G1/S arrest in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 28 publications
4
74
1
Order By: Relevance
“…Our data show that in fact lamin A/C binds the CDKN1A promoter and the interaction between lamin A/C and HDAC2 favors HDAC2 recruitment (Noh et al, 2011), as suggested by reduced deacetylase binding in HGPS, despite increased protein levels.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our data show that in fact lamin A/C binds the CDKN1A promoter and the interaction between lamin A/C and HDAC2 favors HDAC2 recruitment (Noh et al, 2011), as suggested by reduced deacetylase binding in HGPS, despite increased protein levels.…”
Section: Discussionsupporting
confidence: 66%
“…It was demonstrated (Peng et al, 2015) that HDAC2 is recruited to CDKN1A promoter by FOXO3a and regulates p21 expression in cerebellar granule neuron. Furthermore, HDAC2 has been shown to suppress p21 expression in human hepatocellular carcinoma via its binding to an Sp1‐binding site (Noh et al, 2011). On the other hand, it has been demonstrated that lamin A/C establishes direct interactions with histone deacetylases including SIRT1 (Cenni et al, 2014; Liu et al, 2012), SIRT6 (Ghosh, Liu, Wang, Hao, & Zhou, 2015), and HDAC1 (Kubben et al, 2016), while lamin partners at the nuclear envelope such as emerin, BAF, and LAP2beta interact with HDAC3 (Demmerle, Koch, & Holaska, 2013) or HDAC2 (Tsai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that aberrant expression (highly expressed) of HDAC2 in hepatocellular carcinomas and its mitogenic functions are associated with the transcriptional regulations of cell-cycle regulators (7). To generalize our findings, we examined HDAC2 gene expressional data in a large cohort of patients with hepatocellular carcinoma, available from the NCBIGEO database (accession numbers GSE14520, GSE16757, and GSE25097).…”
Section: Resultsmentioning
confidence: 90%
“…S1C). In addition, we performed GSEA using three different cancer cell lines (liver, lung, and gastric cancer) to confirm HDAC2 signatures in these cell lines (7,9,10). Indeed, GSEA showed that EGFR system-related gene elements were commonly enriched in HDAC2 signatures observed in these cell lines (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation